Help and Support to Victims of Terrorism – International Standards - Čopelj, Lejla (Kriminalističke teme, 2024)
According to available data from security agencies around the world, terrorism represents a leading security challenge as one of the most complex, challenging and dangerous political and security phenomena. Terrorist organizations or groups direct their destructive activities to civilian targets in order to cause losses, cause fear and insecurity among the population and to send messages to governments about the importance of fulfilling their radical goals. Due to the large-scale terrorist attacks around the world since the beginning of the 21st century, the fight against terrorism arouses the increasing awareness of the professional public, and in this regard, help and support for victims of terrorism are taking more and more place and attention both in international instruments and in the domestic legislation of states. In theory, there are many definitions of terrorism, but not a single and harmonized one. By looking at the large number of definitions created by international organizations and the aca- demic community, we can conclude that all definitions have at least three main characteristics in common: the intention to cause death or serious bodily injury and damage to property, the targets are often randomly selected persons, especially civilians, with the purpose of in- timidate the population or compel a government or international organization to do or refrain from doing an act. Just as it is difficult to reach a consensus on the definition of terrorism, it also seems prob- lematic to define the term ‘victim’ in the context of terrorist attacks. There are three main questions and areas for analysis and study in the field of assistance and support to victims of terrorism: specific needs of victims of terrorism, differences in the effect of different forms of terrorism on victims, and the question of whether the specificity of the attack merits different approaches to the victim.